Philodendron scandens Heart Leaf Philodendron: FPS472/FP472, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides a comprehensive overview of the heart leaf philodendron (Philodendron scandens), detailing its characteristics, growth habits, and care requirements. It describes the plant’s adaptability to indoor and outdoor environments, highlighting its tolerance for low light and its potential to grow as a ground cover or climbing plant. The document also outlines the plant’s physical attributes, including leaf shape, size, and color, as well as its moderate growth rate and soil preferences. Additionally, it addresses the plant’s pest and disease resistance, propagation methods, and optimal planting conditions. Original publication date October 1999.